Israel: A Simple Guide to the Most Misunderstood Country on Earth : A Simple Guide to the Most Misunderstood Country on Earth - Tishby, Noa, 1977- (New York : Free Press, 2021)
"A personal, spirited, and concise chronological timeline spanning from Biblical times to today that explores one of the most fascinating countries in the world--Israel"--.
While everyone seems to have a strong opinion about Israel, how many people actually know the facts? Tishby creates an accessible and dynamic portrait of a tiny country of outsized relevance. Through bite-sized chunks of history and deeply personal stories, she chronicles her homeland's evolution, beginning in Biblical times and moving forward to cover everything from WWI to Israel's creation to the real disputes dividing the country today. Tackling popular misconceptions with an abundance of facts, she offers a clear, intimate account of the richly cultured country of Israel. -- adapted from jacket
Dream. A brief history of me ; A brief history of the land of Israel ; A brief history of the Middle East in the last century ; A brief history of Zionism ; Chasing that dream -- Do. A state is born ; A tug of war and peace ; Settlements ; Arabs -- Be. BDS ; May the melting pot no melt us all ; Up up nation ; What's with the obsession, world? -- Afterword: This is a promise -- Appendix: A much quicker guide.
new book 2024 winter.
Includes bibliographical references (pages 311-321) and index.
Keywords: Tishby, Noa, -- 1977-; Tishby, Noa, -- 1977-; HISTORY / Asia / General; Actresses -- Israel -- Biography; Jews -- History; Arab-Israeli conflict; Israel -- History; Israel; Eretz Israel -- History; Israel -- History; History